2015
DOI: 10.1590/01000683rbcs2015081
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxides: Nanomaterials for Applications in Agriculture

Abstract: The current research aims to introduce Layered Double Hydroxides (LDH) as nanomaterials to be used in agriculture, with particular reference to its use as storage and slow release matrix of nutrients and agrochemicals for plant growing. Structural characteristics, main properties, synthesis methods and characterization of LDH were covered in this study. Moreover, some literature data have been reported to demonstrate their potential for storage and slow release of nitrate, phosphate, agrochemicals, besides as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 47 publications
1
55
0
1
Order By: Relevance
“…These materials are a subject of great technological interest because of their catalytic (Liu et al, 2008;Tong et al, 2010;Xu et al, 2011;Yu et al, 2014;Fan et al, 2014), electrochemical (Indira et al, 1994;Jayashree and Kamath, 2002; and photochemical (He et al, 2004;El-Toni et al, 2006) properties, which have already found many applications in modern industry (Li and Duan, 2006). Moreover LDHs have found applications in pharmacology and biochemistry (Choy et al, 2001;Aisawa et al, 2001;Arco et al, 2004;Nalawade et al, 2009;Conterosito et al, 2013) and are considered as important materials for solution of the number of environmental and agricultural issues (Génin et al 2008(Génin et al , 2013(Génin et al , 2014aZümreoglu-Karan and Ay, 2012;Tiwari and Syvajarvi, 2014;Radha and Navrotsky, 2014;Manohara, 2014;Benício et al, 2015). LDHs have been discussed as probable matrices for the origin of life as prebiotic information storage and transfer compounds (Greenwell and Coveney, 2006), though this idea has received some criticism later (Krivovichev et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…These materials are a subject of great technological interest because of their catalytic (Liu et al, 2008;Tong et al, 2010;Xu et al, 2011;Yu et al, 2014;Fan et al, 2014), electrochemical (Indira et al, 1994;Jayashree and Kamath, 2002; and photochemical (He et al, 2004;El-Toni et al, 2006) properties, which have already found many applications in modern industry (Li and Duan, 2006). Moreover LDHs have found applications in pharmacology and biochemistry (Choy et al, 2001;Aisawa et al, 2001;Arco et al, 2004;Nalawade et al, 2009;Conterosito et al, 2013) and are considered as important materials for solution of the number of environmental and agricultural issues (Génin et al 2008(Génin et al , 2013(Génin et al , 2014aZümreoglu-Karan and Ay, 2012;Tiwari and Syvajarvi, 2014;Radha and Navrotsky, 2014;Manohara, 2014;Benício et al, 2015). LDHs have been discussed as probable matrices for the origin of life as prebiotic information storage and transfer compounds (Greenwell and Coveney, 2006), though this idea has received some criticism later (Krivovichev et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their extraordinary properties, LDH materials are widely used in a large variety of applications, e.g., catalysis, drug delivery systems, adsorbents, among many others [32]. LDHs can be synthesized directly via co-precipitation [33], the sol-gel method [34,35], the self-combustion method [36], or the homogeneous alkalization route [37,38], or indirectly by the modification of pre-synthesized LDHs via anion exchange methods aiming at the substitution of the interlayer anions by other anions or even medicines (producing drug delivery systems), or reconstruction and rehydration methods [39]. It should be noted that the direct homogeneous alkalization route is especially suitable for synthesis of highly crystalline LDHs [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…where M 2+ is a bivalent metal ion (such as Ca 2+ , Mg 2+ , Zn 2+ ); M 3+ is a trivalent metal ion (such as Fe 3+ , Al 3+ , Mn 3+ ) and A n-is the interlayer anion. LDHs occur in nature as minerals or can be synthetized at relatively low cost in an environmentally friendly manner, characterized as green chemistry [9,[13][14][15][16]. The fine texture of LDHs can limit their applications.…”
Section: Introduction mentioning
confidence: 99%